Implementasi Program Pembinaan Kemandirian pada Warga Binaan Pemasyarakatan (WBP) di Lapas Kelas IIB Pasuruan - Dinta Fernanda Maulidya (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
This study examines the implementation of the independence coaching program for inmates at Pasuruan Class IIB Prison. The background of this study is based on the importance of improving the competence and readiness of inmates for social reintegration through an effective coaching program. The main objectives of the study are to analyze the implementation process, obstacles faced, and the positive impacts of the program. The method used in this study is descriptive qualitative with interview, observation, and documentation techniques. Data were analyzed through data reduction, data presentation, and drawing conclusions based on policy implementation theory according to Merilee S. Grindle, as well as triangulation of sources and methods to ensure data validity. The study findings show that the success of the program is supported by cross-sector stakeholder involvement and the benefits felt by inmates, both in terms of improving skills and additional income. The conclusion of the study confirms that the implementation of the program is going quite well, but there are still challenges related to resources, facilities, and environmental factors that need to be reconsidered, especially when moving to an integrated prison. Although there are several obstacles, employees and inmates can overcome these problems with appropriate solutions according to field conditions